The Effect of Learning Strategies and Learning Autonomy on Civics Learning Outcomes - Hamuni; Muhammad Idrus; Aswati (Universitas Pendidikan Ganesha, 2022)
Most students believe civics education is a complex and difficult field of science, resulting in a low score. The challenges that arise can be overcome through the use of innovative learning strategies.The focus of this study is to analyses the impact of learning strategies and learning autonomy on student Civics learning outcomes. This study's sample consisted of 60 students chosen at random using a multistage random sampling procedure. The information in this study was collected using test instruments and questionnaires.The statistical analyses were performed using variance analysis (ANOVA) with a significance level of = 0.05.The findings revealed that: Civics learning outcomes were higher among students taught with problem-based learning strategies than students taught with project-based learning strategies; and there was a significant interaction between learning strategies and learning autonomy on Civics learning outcomes. This study concluded that students with high learning autonomy should be taught utilizing problem-based learning techniques and project-based learning strategies because they can increase student Civics learning outcomes. Students with minimal learning autonomy who are taught problem-based learning strategies and project-based learning strategies, on the other hand, show no significant differences in Civics learning outcomes.